THE TIME IN THE STUDENT’S LIFE THROUGH THE EYES OF A SOCIOLOGIST - Polina A. Ambarova; Garold E. Zborovsky (Высшее образование в России, 2016)
Student’s temporal behavior strategies as a special way of formation and realization of their human capital are considered. The article contains data of theoretical and empirical research of students’ temporal behavior strategies. Contradictions of temporal consciousness of students, the reasons of their emergence are shown. The article presents some types of students’ temporal behavior strategies.